Analisis Partisipasi dan Kepuasan Kelompok Tani Terhadap Kinerja Penyuluh Pertanian di Kecamatan Maritenggae, Kabupaten Sidenreng Rappang - Sumantri, Iswan; Haryono, Iranita; Wulandary, Ayu (Journal of Agribusiness Science and Rural Development, 2024)
Farming is a noble activity that contributes to the preservation of nature and the lives of other living things. The government can utilize agricultural extension as a policy tool to encourage the progress of this sector. However, farmers have the right to accept or reject advice from agricultural extension agents. So why is this study very important to measure how much participation of farmer groups in the agricultural extension work program In Maritenggae District, Sidenreng Rappang Regency, the aim of this study was to ascertain the degree of engagement and satisfaction of farmer groups in the agricultural extension work program. This study was carried out in the Maritenggae District of the Sidenreng Rappang Regency between March and May of 2024. With a sample of 30 farmer groups, the study's population consisted of 861 members of farmer groups in Maritenggae District, Sidenreng Rappang Regency. Questionnaires were used in conjunction with direct interviews to obtain data. Importance Performance Analysis (IPA) and descriptive analysis were the analytical methods employed in this investigation. The study's findings indicate that farmer groups' engagement had an average percentage value of 89%, with a very participating category. Although the outcomes of the, Farmer groups must be active and participate in extension services held by extension workers so that they can learn and apply the knowledge provided. Extension workers must also help farmer groups improve their skills and abilities to increase the productivity of their farming businesses, agricultural extension workers must also improve their performance to farmer groups.